The Role of Corporate Value Clusters in Ethics, Social Responsibility, and Performance: A Study of Financial Professionals and Implications for the Financial Meltdown - Jin, K. Gregory; Drozdenko, Ronald; DeLoughy, Sara (2013)
This article delves into a potential mindset that may be responsible for the recent financial meltdown. Research relating to this mindset from different perspectives is reviewed. The findings from this literature review are used to create a conceptual framework for the empirical, ethical, and corporate social responsibility study of financial professionals. Data were collected from a survey of the professional membership of a large national association of financial professionals. This article reports the results of the analysis of data relative to the relationships among the four constructs—financial professionals’ perceived organizational value clusters, ethics, corporate social responsibility, and corporate performance. The findings indicate that organizational core values significantly affect corporate ethics, social responsibility, and financial performance. We propose that organizations in the financial industry can move toward being more ethical and socially responsible by adopting organic core values (e.g., democratic, open, trusting, enterprising, creative, stimulating) and moving away from mechanistic values (e.g., structured, regulated, procedural, authoritarian, closed, callous). We also found the adaptation of organic core values does not require the organization to suffer a loss in financial performance.
Keywords: Corporate Governance; Corporate ethics/social responsibility/performance; Corporate core value clusters; Financial meltdown; and cultural model; Social; Moral; Ethical mind-set